Crohn’s Disease with Gastric Involvement: A Case Report - Melo, Amanda Gabriele Alves Cobiniano de; Loureiro, Amanda Guimarães; Silva, José Leandro Nascimento da; Marinho, Luann Bambach; Bastos, Dauana Arruda de Oliveira (Brazilian Journal of Case Reports, 2025)
Inflammatory bowel disease (IBD) encompasses acute or chronic inflammatory processes affecting the gastrointestinal tract, primarily comprising Crohn’s disease (CD) and ulcerative colitis (UC). CD is a transmural and recurrent condition that can affect any segment of the gastrointestinal tract, with gastric involvement being rare, occurring in less than 5% of cases. This report aims to describe a rare case of Crohn’s disease with exclusive gastric manifestation, highlighting the diagnostic challenges and therapeutic strategies employed. A comprehensive clinical and laboratory investigation was conducted, including outpatient interview, laboratory tests, upper gastrointestinal endoscopy, and computed tomography. The findings were analyzed to rule out other diseases with similar symptoms. The diagnosis of Crohn’s disease confined to the stomach was confirmed in a patient whose only complaint was nausea. The treatment was managed clinically and pharmacologically, with no indication for surgical intervention. During follow-up, up to the time of this report, the patient remained free of relapses or complications. Therefore, gastric Crohn’s disease is a rare and diagnostically challenging condition that requires a multidisciplinary approach to exclude other pathologies. Appropriate clinical management allowed disease control and the avoidance of complications, underscoring the importance of early diagnosis and continuous follow-up.